Peran Instagram sebagai Media Dakwah pada Masa Pandemi - Farhan Ar’Rayyan; Kamalludin Kamalludin; Suhendra Suhendra (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The Covid-19 pandemic is an abnormal condition that has an impact on various aspects of life ranging from social, educational, economic, including the impact on da'wah activities. Barriers to social interaction in the practice of syi'ar Islam are indirectly a problem that must be resolved. The use of social media is a possible alternative tool in the midst of current policies. One community that is able to adapt by utilizing social media as a medium of da'wah is the Penuntut Ilmu Bogor community. Therefore, in this study the researcher wanted to find out how the role of social media Instagram as a medium of da'wah during the pandemic and how the da'wah strategy was carried out by the community. The research method used is qualitative, with data collection techniques of observation, interviews and documentation. The results obtained in this study, Instagram social media as a medium of da’wah during the pandemic has various roles by utilizing the features contained in it, besides that Instagram acts as a communication medium, sharing media, charity media, promotional media and storage media. The da'wah strategy is divided into 3 stages, namely the planning stage, the implementation stage, and the assessment stage. there is a da’wah strategy used is da’wah bil hal, da’wah bil qolam and da’wah bil hal.